FEATURES OF VASCULAR DECIDUA IN THE WOMEN WITH INTRAUTERINE SEPTUM - Gladchuk, V. I. (Journal of Education, Health and Sport, 2015)
Gladchuk V. I. Features of vascular decidua in the women with intrauterine septum = Oсобенности сосудистой системы децидуальной оболочки у женщин с внутриматочной перегородкой. Journal of Education, Health and Sport. 2015;5(12):299-307. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35435 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A299-307 http://pbn.nauka.gov.pl/works/681707 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 16.12.2015. FEATURES OF VASCULAR DECIDUA IN THE WOMEN WITH INTRAUTERINE SEPTUM OСОБЕННОСТИ СОСУДИСТОЙ СИСТЕМЫ ДЕЦИДУАЛЬНОЙ ОБОЛОЧКИ У ЖЕНЩИН С ВНУТРИМАТОЧНОЙ ПЕРЕГОРОДКОЙ V. I. Gladchuk В. И. Гладчук Odessa National Medical University, Odessa, Ukraine Одесский национальный медицинский университет, Одесса, Украина Summary The density of microcirculatory vessels in parietal and basal parts of deciduas (PD and BD) was less when compared with the control by 28,8% (P<0,05) and 29,7% (P<0,05) correspondently in women with complete intrauteral septum who had infertility period, which lasted not less than 5 years (from 5,0 up to 13,5 years) with the consequent first trimester miscarriage have been investigated. The general square of microcirculatory vessels in secretory part of decidual endometrium exceeded control value by 24,0% (P<0,05), while lumen square of vessels in PD and BD exceeded control data by 57,3% and 50,5% (P<0,05) correspondently. Established differencies of microcirculatory vessels are considered as a pathogenetic of the infertility and miscarriage in women with intrauteral septum. Key words: vessels of decidua, intrauteral septum, miscarriage, infertility. Реферат У женщин с полной внутриматочной перегородкой, у которых наблюдался период бесплодия период бесплодия составил не менее 5 лет (от 5,0 до 13,5 лет) с последующим спонтанным прерыванием беременности в первом триместре, плотность сосудистой сети в париетальной и базальной частей децидуальной оболочки (ПД и БД) была меньше чем в группе контроля на 28,8% (P<0,05) и на 29,7% (P<0,05) соответственно. Общая площадь сосудистой сети в секреторном эндометрии децидуальной оболочки была на 24,0% больше, чем в контроле (P<0,05), а площадь поперечного сечения сосудов в ПД и БД превышала соответствующие показатели в группе контроля – соответственно на 57,3% и на 50,5% (P<0,05). Установленные различия сосудистой сети рассматриваются в качестве патогенетических механизмов развития бесплодия и невынашивания при наличии внутриматочной перегородки. Ключевые слова: васкуляризация децидуальной оболочки, внутриматочная перегородка, невынашивание, бесплодие.